Study on Stress Management through Psychoneurobics: Understanding and coping with stress (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Stress is the manner in which that we respond physically, rationally and sincerely to different conditions, changes and requests in our lives. Numerous understudies and resources encounter differing dimensions of stress every semester. As indicated by Walter Canon (1929) we require stress to assist us with an intense reaction, for example, in battle or flight reaction. Battle or flight reaction, neglect, loss of mental fixation, tension and dread, dejection, extraordinary annoyance and dissatisfaction, family strife, social withdrawal, and loss of enthusiasm for exercises.